Surface modification of nanoscale energy electrodes using atomic layer deposition. - Hay, Zao Hiong. (2012)
In this thesis, the use of atomic layer deposition (ALD) was applied on hydrothermally grown rutile-TiO2 nanorods on fluorine-doped tin oxide (FTO), cultivating a nanorod array of anatase-rutile TiO2 heterojunctions. Thickness of the ALD thin film for optimal photocurrent generation and electron transport properties was determined through a series of photoelectrochemical tests and reflectivity and quantum efficiency (QE) plots. A visual understanding of the nanostructures was achieved through SEM images. Further hydrothermal growth after ALD was attempted with some success.